Angiogenesis in odontogenic keratocyst and dentigerous cyst: Evaluation of JunB and VEGF expression - Donia Sadri; Sareh Farhadi; Pegah Nourmohamadi (Wolters Kluwer Medknow Publications, 2019)
Background: Nowadays, different clinical behaviors of odontogenic cysts, little information about their biological agents, importance of diagnosis, and early diagnosis of these lesions have encouraged the researchers to conduct new studies. JunB acts as a regulator of vascular endothelial growth factor (VEGF) protein production and affects vessel proliferation and tissue angiogenesis. Hence, this study was conducted to compare angiogenesis through VEGF and JunB expression in odontogenic keratocysts (OKCs) and dentigerous cysts (DCs). Materials and Methods: A total of 25 paraffin blocks of OKCs and 25 DCs were included in this experimental descriptive cross-sectional study, and immunohistochemical expression of VEGF and JunB was evaluated. Percentage and score of expression were recorded for each sample, and independent t-test, Mann-Whitney U, and Spearman statistical tests were run to analyze the data. The statistical significance level was set at <0.05. Results: From 50 studied samples, 39.6% belonged to women and 60.4% belonged to men, with mean age of 34.2 ± 1.7 years. The mean percentages of JunB expression were 52.88 ± 17.35 and 74.6 ± 18.55 for DC and OKC samples, respectively. This expression was significantly higher in OKC than DC, and it had significantly higher scores as well (P= P = 0.0001 and 0.00033, respectively). The means of VEGF were 20.2% ±11.86 and 52.6% ±19.98 in DC and OKC samples, respectively. The mean VEGF expression was significantly higher in OKC than DC (P = 0.045), and it had significantly higher scores, too (P = 0.000). Furthermore, there was a significant correlation between VEGF and JunB expression in the studied samples (rs = 0.3 and P= 0.005). Conclusion: Based on the results of this study, it seems evaluation of angiogenesis through JunB expression can be helpful in the prediction of more aggressive behavior in pathologic lesions such as OKC.